2023
DOI: 10.1002/iid3.779
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin deficiency suppresses allergic asthma and enhances efferocytosis via PPAR‐γ/MFG‐E8 regulation in macrophages

Abstract: Efferocytosis can resolve airway inflammation and enhance airway tolerance in allergic asthma. While previous work has reported that progranulin (PGRN) regulated macrophage efferocytosis, but it is unclear whether PGRN‐mediated efferocytosis is associated with asthma. Here, we found that in an ovalbumin (OVA)‐induced allergic asthma model, the airway inflammation was suppressed and the apoptosis in lung tissues was ameliorated in PGRN‐deficient mice. In contrast, PGRN knockdown in human bronchial epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…PPAR-γ plays an important role in the inflammatory response, inducing the oxidative metabolism of macrophages by upregulating the oxidation of fatty acids and mitochondrial biosynthesis ( 32 ). PPAR-γ increased the expression of SIRT1 in macrophages and upregulated SIRT1 increased the secretion of IL-10, thus playing an anti-inflammatory role ( 33 ).…”
Section: Airway Allergic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-γ plays an important role in the inflammatory response, inducing the oxidative metabolism of macrophages by upregulating the oxidation of fatty acids and mitochondrial biosynthesis ( 32 ). PPAR-γ increased the expression of SIRT1 in macrophages and upregulated SIRT1 increased the secretion of IL-10, thus playing an anti-inflammatory role ( 33 ).…”
Section: Airway Allergic Inflammationmentioning
confidence: 99%
“…Recent reports have explored treatment options for allergic inflammation, including drugs that target SIRT1 to provide relief for allergic diseases ( Table 1 ). Among the drugs that have demonstrated effectiveness in alleviating AAI are Allopurinol, GW9962, Hylocereus undatus flower (HUF), Pterostilbene (Pts), Gentiopicroside (GPS), and EX-527 ( 26 , 33 , 43 , 51 , 112 , 113 ). Studies have found that SIRT1 expression in immune cells can help relieve allergic rhinitis, and the use of SIRT1 agonist resveratrol has shown promise in treating AR ( 64 , 71 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Apoptotic eosinophils and neutrophils are common in asthma [ 185 ]. Efferocytosis is a process that removes apoptotic cells during the inflammatory resolution stage and is essential for returning the lung to homeostasis [ 186 ]. Defective efferocytosis has been linked to secondary necrosis and release of damage signals that further enhance inflammation [ 185 , 187 ].…”
Section: Inflammatory Resolutionmentioning
confidence: 99%
“…The accumulated apoptotic cells suppressed the release of anti-inflammatory mediators such as IL-10 and TGF-β. And the shedding of Axl was also related to the damage of efferocytosis, while IFN could restore the expression of Axl on airway macrophages [107][108][109]. Research has shown that the expression of Neurofibroin-2 (Nrp2) is increased in neutrophil asthma mice and is a negative regulatory factor for neutrophil asthma.…”
Section: Asthmamentioning
confidence: 99%